Abdominal Wall Hydatid Cyst: Case Report and Review of Literature. (16th August 2012) - Abhishek, V.; Patil, Vijayraj S.; Mohan, Ullikashi; Shivswamy, B. S.
Abstract : A 60-year-old woman presented with a swelling in right paraumbilical region of one-year duration. Examination revealed a painless cystic swelling 15 × 10 cm with cough impulse. Ultrasound and CECT abdomen showed a subcutaneous cystic swelling with intramuscular extension. No other intraabdominal cystic lesions were found. Surgical exploration showed a cystic lesion adherent to peritoneum without any intraperitoneal extension. Cyst was carefully excised without any spillage. Gross specimen on opening showed multiple daughter cysts consistent with hydatid cyst, confirming the diagnosis of solitary abdominal wall hydatid cyst.